Pemberdayaan Kader Remaja dalam Upaya Pencegahan Stunting dengan Deteksi Gizi Remaja untuk Persiapan Kehamilan di Desa Sembubuk Kabupaten Muaro Jambi - Murtiyarini, Ika; Wuryandari, Ajeng Galuh (Universitas Baiturrahim, 2025)
Stunting is a long-term nutritional problem in Indonesia that has a big effect on the growth and development of children and the quality of the country's future human resources. Because people in rural areas don't understand it, it is still very common. To solve this problem, this community service project wants to give young people the tools they need to be agents of change in stopping stunting, especially when it comes to preparing for a healthy pregnancy. The methods used include coaching and mentoring, as well as training on getting ready for marriage, planning for pregnancy, and nutrition. After that, there was practical nutrition screening through anthropometric measurements and the making of health promotion materials. The activities led to a big improvement in the adolescent cadres' ability to find out about nutrition and stunting, as well as their ability to take anthropometric measurements. This programme to empower young people has worked, giving youth cadres a bigger role in public health efforts. It could be used as a model for empowering young people in other areas with similar stunting problems.